Pengaruh Model Pembelajaran Realistic Mathematics Education (RME) terhadap Pemahaman Konsep Peserta Didik Sekolah Dasar - Dorisno, Dorisno; Aisyah, Hijrafa; Rahmawati, Dwi Nur Umi; Frasandy, Rendy Nugraha (SITTAH: Journal of Primary Education, 2024)
The problem is motivated by educators, such as the use of models in learning is not optimal so that there is no activity of students constructing their own concepts and the tendency of students to memorize mathematical formulas instead of understanding it happens so that what they learn is easy to forget. The study aims to determine whether there is a difference when applying the Realistic Mathematics Education (RME) model to students' concept understanding with no RME learning model applied. The solution offered to find a way out is to apply the RME learning model. This study uses a type of quantitative research with the Quasy Experiment method. The population of this study were all students of class V A, VB and V B SDN 02 Payakumbuh. Researchers use random sampling because the number of objects tends to be large. The class selected as the experimental class is class V C and class V B control class. The data collection technique used tests and data analysis techniques were carried out by normality test, homogeneity test, and hypothesis testing using SPSS 29. The results showed the average posttest score of the experimental class was 83.91 and the control class was 78.55. Based on the results of the t-Test output: Two-Sample Assuming Equal Variances obtained a tcount value of 2.06> ttable 1.994. So according to the basis for decision making in the Two-Sample Assuming Equal Variances test, Ha is accepted and H0 is rejected, meaning that "the application of the RME learning model provides a better understanding of concepts to students than using a direct learning model in learning grade V mathematics SDN 02 Payakumbuh".